A description of the new tardigrade Macrobiotus reinhardti (Eutardigrada: Macrobiotidae, harmsworthi group) with some remarks on the oral cavity armature within the genus Macrobiotus Schultze - Michalczyk, Łukasz; Kaczmarek, Łukasz (Zootaxa, 2003)
Six moss samples collected in the Greek part of Cyprus contained tardigrades and their eggs, also adults and eggs of a new species, Macrobiotus reinhardti sp. nov. The new species belongs to the harmsworthi group and differs from the most similar M. stellaris Du Bois-Reymond Marcus in details of the egg shell and some morphometric characters. In this paper we also propose new terminology describing the oral (mouth) cavity armature within the genus Macrobiotus Schultze, on the basis of Scanning Electron Microscopy investigation of two macrobiotid species. According to the new terminology, all groups of cuticular structures in the oral cavity should be described as bands of teeth.